ЕЛЕКТРОСТАТИЧНЕ ПОЛЕ В ПОВІТРЯНОМУ ПРОМІЖКУ СИСТЕМИ ПЛОСКО-ПАРАЛЕЛЬНИХ ЕЛЕКТРОДІВ ДЛЯ ОБРОБКИ КРАПЕЛЬ ВОДИ БАР’ЄРНИМ РОЗРЯДОМ - Крищук, Р.С.; Берека, В.О. (Інститут електродинаміки НАН України, Київ, 2025)
This study investigates the electrostatic field in a discharge chamber (DC) designed for water purification from organic pollutants using pulsed barrier discharge (PBD) technology. The DC consists of vertical plane-parallel electrodes, with an air gap containing water droplets between them, and one of the electrodes is insulated from the air gap by a dielectric (barrier). The research employs computer modeling in both two-dimensional and three-dimensional setups. Therefore, the aim of this work is to compare the distribution of the electrostatic field intensity of PBD in the air gap and the electrical capacitance of the DC to establish the optimal distance between droplets and to determine the calculation error using the two-dimensional DC model. Electrostatic field modeling was performed using the Poisson equation and the finite element method. Calculations were performed for two-dimensional and three-dimensional models with conditions of a droplet diameter of 1 mm, a gas gap length of 3.36 mm, and an applied voltage of 3 kV. The influence of droplet conductivity and the distance between them on the characteristics of the electrostatic field in the gas medium and in the droplets was investigated. A comparison of the calculated capacitance values of the DC in the two-dimensional and three-dimensional models depending on the distance between the droplets was conducted. The research results can be used in the application of electro-discharge technology based on pulsed barrier discharges in water treatment systems, specifically in selecting the parameters for the movement of the treated liquid in the plasma zone. References 10, figures 7.